Digital First Primary Care for those with multiple long-term conditions: a rapid review of the views of stakeholders - Jennifer Newbould; Lucy Hocking; Manbinder Sidhu; Kelly Daniel (NIHR Journals Library, 2024)
Background General practices are facing challenges such as rising patient demand and difficulties recruiting and retaining general practitioners. Greater use of digital technology has been advocated as a way of mitigating some of these challenges and improving patient access. This includes Digital First Primary Care, when a patient's first contact with primary care is through a digital route, either through a laptop or smartphone. The use of Digital First Primary Care has been expedited since COVID-19. There is little evidence of staff experiences of using Digital First Primary Care with more complex patients, such as those with multiple long-term conditions. Objective To understand the experiences of those with multiple long-term conditions of Digital First Primary Care from the perspectives of healthcare professionals and stakeholders. Design This was a qualitative evaluation, comprised of four distinct work packages: Work package 1: Locating the study within the wider context, engaging with literature, and co-designing the study approach and research questions with patients. Work package 2: Interviews with health professionals working across general practice and key expert topic stakeholders, including academics and policy-makers. Work package 3: Analysis of data and generation of themes, and testing findings with patients. Work package 4: Synthesis, reporting and dissemination. Results The study commenced in January 2021 and in total 28 interviews were conducted with 14 health professionals and 15 stakeholders between January and August 2022. From the perspective of health professionals, Digital First Primary Care approaches could enable patients to speak with a clinician more quickly than traditional approaches. Those with multiple long-term conditions could submit healthcare readings from home, though health professionals felt patients may struggle navigating digital systems not designed to capture the nuances associated with living with multiple conditions. Clinicians expressed preferences for seeing patients face-to-face, particularly those with multiple long-term conditions, to identify non-verbal cues about a patient's health. Digital First Primary Care approaches provided an opportunity for clinicians to engage with the carers of patients living with multiple long-term conditions, yet there were concerns around obtaining consent and confidentiality. There remain debates among stakeholders about the nature and extent to which Digital First Primary Care impacts on staff workload. Limitations At the time of data collection, general practices were facing considerable pressure to deliver care and respond to the COVID-19 pandemic. While it was originally intended that the study would include interviews with patients with multiple long-term conditions and their carers, none of the general practices that took part in the study were willing and/or able to recruit patients and carers in the time available. Conclusions The rapid implementation of Digital First Primary Care, at a time of immense pressures, meant there has been little time for considering the impact on patients, including those with multiple long-term conditions. The impacts on care continuity depended largely on how surgeries implemented their approaches. Staff and stakeholders felt that Digital First Primary Care, as an additional route for accessing primary care, could be useful for patients with multiple long-term conditions but not at the expense of face-to-face consultations. Future work Future research obtaining patient and carer views of digital-first approaches, understanding the impacts on carers and how approaches are designed with patients with more complex conditions in mind, is essential. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 16/138/31) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 21. See the NIHR Funding and Awards website for further award information. Plain language summary Healthcare professionals want to provide the best primary care in the face of increasing pressures, as well as improve access to care for patients. Digital First Primary Care is one response to this situation, when a patients' first contact with primary care is through a digital route, either through a laptop or smartphone. Online systems allow the patient to provide information to their practice about their symptoms or needs and request a response from a health professional. Our study aimed to understand how Digital First Primary Care works for healthcare professionals providing care to increasing numbers of patients with multiple long-term conditions and their carers. Firstly, we examined the relatively limited existing findings and then interviewed healthcare professionals and key stakeholders experienced in digital approaches within primary care (e.g. from policy organisations, universities and the National Health Service). While we attempted to speak to patients and carers directly, unfortunately the pressures in general practice meant we were unable to do so. However, the study was co-designed with patients. Healthcare professionals and stakeholders felt that patients with multiple long-term conditions faced additional challenges with the use of Digital First Primary Care compared to other patients. For example, they reported difficulties navigating online forms and not being able to speak with a general practitioner who knew them well. There were differing views from healthcare professionals and stakeholders about how far Digital First Primary Care could help staff in general practice and enhance care. For some clinicians, the workload was easier to manage and some simple tasks (e.g. sick notes) could be completed quickly. This could reduce stress for staff and mean more patients could be seen per day. Others felt that the digital system had shortcomings. This could be important for patients with multiple long-term conditions; for example, when a digital form may not fully inform the general practitioner as to the exact nature of the problem, potentially requiring a further follow-up appointment. Health professionals reported that carers of patients with multiple long-term conditions generally liked the new systems as they helped to improve contact with general practice staff. The summary was co-authored by members of the BRACE Patient and Public Involvement group. Scientific summary Background Digital First Primary Care has become widespread in England, particularly since the COVID-19 pandemic. Digital First Primary Care is when a patients' first contact with primary care is through a digital route, either through a laptop or smartphone. The design of Digital First Primary Care platforms varies by commercial provider, although the main principles are the same. The patient inputs their symptoms and concerns through a digital platform, either via a set of questions within a digital algorithm or through a free text submission. The patient is then given an appropriate response, which could be from a staff member within the practice or automatically generated by the algorithm. The consultation which results may be traditional in nature, for example by telephone or face-to-face, or be in the form of a message from a health professional to a patient or a video consultation. These approaches have been advocated by policy-makers in England since 2016, as it is believed they can enable clinicians to prioritise the care of patients. Despite the policy shift towards digital approaches, most general practitioner (GP) surgeries were not operating in this way in early 2020, with an analysis of primary care data suggesting that 13-15% of consultations were conducted remotely in January 2020. The COVID-19 pandemic has seen a rapid change in modes of service delivery in general practice, with all GP surgeries having to quickly adapt their services and offer some form of non-face-to-face consultation, to prevent viral transmission. Several studies have been conducted on the use of digital approaches in the National Health Service (NHS). The findings from these studies are wide-ranging. To summarise, digital approaches can provide a benefit to both staff and patients (e.g. greater convenience, including no need to travel to a general practice, and better monitoring of conditions), although there are some challenges.